Community Ageing With Health And Dignity Through A Service-Learning Initiative - Hiu Lam Yee (Asia Pacific Journal of Health Management, 2020)
Background: A new compulsory service-learning subject was introduced in the Practices of Health Promotion module of Bachelor of Science in Applied Sciences (Health Studies), run by School of Professional Education and Executive Development, The Hong Kong Polytechnic University. It aims to develop students’ ability to apply learned principles and concepts of health behaviour from lectures into a community setting, by completing elderly site services arranged at four selected elderly centres.